Sensitivity and specificity of the method used for ascertainment of healthcare-associated infections in the second Slovenian national prevalence survey - Serdt Mojca; Lejko Zupanc Tatjana; Korošec Aleš; Klavs Irena (Sciendo, 2016)
The second Slovenian national healthcare-associated infections (HAIs) prevalence survey (SNHPS) was conducted in acute-care hospitals in 2011. The objective was to assess the sensitivity and specificity of the method used for the ascertainment of six types of HAIs (bloodstream infections, catheter-associated infections, lower respiratory tract infections, pneumoniae, surgical site infections, and urinary tract infections) in the University Medical Centre Ljubljana (UMCL).